PENGARUH RETURN ON ASSET, RETURN ON EQUITY, NET PROFIT MARGIN DAN QUICK RATIO TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR ENERGI PADA MASA PANDEMI COVID-19 : (Pada Sektor Energi Yang Tercatat di Bursa Efek Indonesia Tahun 2019 – 2020) - M. Fikri Arif Setya Pambudi; Ade Irma Suryani Lating; Ashari Lintang Yudhanti; Mulyani Rahman Soulisa (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of partially and simultaneously variables namely Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Quick Ratio (QR) on stock returns. This type of research is quantitative research with secondary data in the form of financial statements (financial statements) of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019 – 2020. This study has the result that the variable Net Profit Margin (NPM) has a significant influence on stock returns, while Return On Assets (ROA), Return On Equity (ROE) and Quick Ratio (QR) do not have a significant effect on stock returns. Meanwhile, all independent variables simultaneously have a significant influence on stock returns. Researchers provide suggestions for future research to use a larger population with a longer time frame and are advised to add more diverse independent variables. For companies to better evaluate various things that can affect stock returns so that issuers can maximize their resources so that they can increase the interest of investors to invest. In addition, for investors to be more selective in terms of fundamental and technical analysis in investing. As well as the government is expected to be more flexible and careful in implementing its regulations.